Decision Making for Acceptance of Physics Teachers with the Fuzzy TOPSIS Method - Fadhilah Dirayati; Samsyuryadi Samsyuryadi; Sukemi Sukemi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Abstract Teachers are the most important human resource in educating students. At SMP Negeri 3 Palembang there is still a great need for teaching staff, namely professional physics teachers. The professional physics teachers selected are those who really have good potential in educating. Teacher selection has not been represented quantitatively so that it is still based on subjective views and thoughts. This study aims to provide a quantitative employee selection decision-making technique through the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Data obtained through interviews with teachers and HRD to get the weight of the criteria at each stage and implemented in teacher candidates. The results obtained were teacher candidate rankings for each stage of selection, so that the teacher was declared to have passed to the next stage or did not pass and could not continue to the next stage. The value with the lowest ranking and does not meet the special criteria will result in the candidate not passing. From the research results, the use of the fuzzy method can make it easier in subjective assessment, and the TOPSIS fuzzy calculation until the final stage results in 3 passing candidates. Keywords—Teacher Selection Decision Making, Fuzzy TOPSIS, Knockout System in Selection Stages